Penatalaksanaan Holistik pada Pasien Anak Usia 8 Tahun dengan Diagnosis Talasemia Melalui Pendekatan Kedokteran Keluarga - Reni Agustin; Reni Zuraida (Majority, 2020)
Beta thalassemia occurs a decreasing of beta chain synthesis. In individuals with Beta Thalassemia, there can be a total loss of the β globin chain (Thalassemia Major) or a partial loss of the β globin chain (Thalassemia Minor). In 2019, there are more than 10,531 Thalassemia patients in Indonesia, and estimated 2,500 newborns with Thalassemia every year in Indonesia. The study was case report, Patient An. N, 8 years old, has been diagnosed with Thalassemia and has fears of growing complaints and does not improve because of late blood transfusion. Limited knowledge about the patient's health condition such as risk factors of thalassemia, complications of thalassemia, prevention of thalassemia, food that need to be avoided, also lack of motivation and encouragement for families to bring their children for blood transfusion routinely are factors that cause problems that occur in patients and families. Holistic and comprehensive management of An. N’s problems has been done by providing counseling to improve the patient's family knowledge.